Application of neural networks in communication network routing - Soo, Ah Bok. (2008)
This project evaluates the application of neural networks for routing in communication networks. Concepts related to routing techniques are first discussed and an overview of neural networks with regard to the model and design is briefly presented. A sample communication network is then used in which each message node is modeled with a neural network. The neural networks are trained and tested with partially known routing information. Routing within the communication network is simulated under fixed and variable traffic conditions, in static and adaptive modes. The results are analyzed for routing accuracy and performance of the neural networks under various traffic conditions. A comparison of the results with those of static routing and those published by other authors is also made. Based on the analysis, it is found that routing with neural networks generally performs not as good as static routing under fixed traffic condition but performs better than static routing under variable traffic condition. The results, however, do not clearly show that routing with neural networks in adaptive mode will improve the routing accuracy significantly as compared to that in static mode.